The Holy Spirit and Power in Luke-Acts and their Significance for Christian Service - Orgu, Cletus C. (NIU Journal of Humanities, 2020)
Most scholars accept the Gospel of Luke and Acts of the Apostles as a single volume and Luke is generally believed to be the author. Lukeâ€™s interest in the Holy Spirit is remarkable. This paper undertakes the exegesis of the texts on the Holy Spirit and Power in Luke-Acts.  It is most likely Luke made a kind of distinction between Holy Spirit and power in some texts of Luke-Acts. Both, it seems are separable and are of God for the empowerment of His people for service. There is therefore the need for the re- reading of those texts. However, the paper does not lose sight of the significance of the Holy Spirit and power for empowerment for service. Keywords: Holy Spirit, Power, Empowerment, Significance, Pentecost.